The Maribor consensus: report of an expert meeting on the development of performance indicators for clinical practice in ART - ESHRE Clinic PI Working Group; Vlaisavljevic, Veljko; Apter, Susanna; Capalbo, Antonio; D'Angelo, Arianna; Gianaroli, Luca; Griesinger, Georg; Kolibianakis, Efstratios M; Lainas, George; Mardesic, Tonko; Motrenko, Tatjana; Pelkonen, Sari; et al. (Human reproduction open, 2021)
STUDY QUESTION: Is it possible to define a set of performance indicators (PIs) for clinical work in ART, which can create competency profiles for clinicians and for specific clinical process steps? SUMMARY ANSWER: The current paper recommends six PIs to be used for monitoring clinical work in ovarian stimulation for ART, embryo transfer, and pregnancy achievement: cycle cancellation rate (before oocyte pick-up (OPU)) (%CCR), rate of cycles with moderate/severe ovarian hyperstimulation syndrome (OHSS) (%mosOHSS), the proportion of mature (MII) oocytes at ICSI (%MII), complication rate after OPU (%CoOPU), clinical pregnancy rate (%CPR), and multiple pregnancy rate (%MPR). WHAT IS KNOWN ALREADY: PIs are objective measures for evaluating critical healthcare domains. In 2017, ART laboratory key PIs (KPIs) were defined. STUDY DESIGN SIZE DURATION: A list of possible indicators was defined by a working group. The value and limitations of each indicator were confirmed through assessing published data and acceptability was evaluated through an online survey among members of ESHRE, mostly clinicians, of the special interest group Reproductive Endocrinology. PARTICIPANTS/MATERIALS SETTING METHODS: The online survey was open for 5 weeks and 222 replies were received. Statements (indicators, indicator definitions, or general statements) were considered accepted when ≥70% of the responders agreed (agreed or strongly agreed). There was only one round to seek levels of agreement between the stakeholders.Indicators that were accepted by the survey responders were included in the final list of indicators. Statements reaching less than 70% were not included in the final list but were discussed in the paper. MAIN RESULTS AND THE ROLE OF CHANCE: Cycle cancellation rate (before OPU) and the rate of cycles with moderate/severe OHSS, calculated on the number of started cycles, were defined as relevant PIs for monitoring ovarian stimulation. For monitoring ovarian response, trigger and OPU, the proportion of MII oocytes at ICSI and complication rate after OPU were listed as PIs: the latter PI was defined as the number of complications (any) that require an (additional) medical intervention or hospital admission (apart from OHSS) over the number of OPUs performed. Finally, clinical pregnancy rate and multiple pregnancy rate were considered relevant PIs for embryo transfer and pregnancy. The defined PIs should be calculated every 6 months or per 100 cycles, whichever comes first. Clinical pregnancy rate and multiple pregnancy rate should be monitored more frequently (every 3 months or per 50 cycles). Live birth rate (LBR) is a generally accepted and an important parameter for measuring ART success. However, LBR is affected by many factors, even apart from ART, and it cannot be adequately used to monitor clinical practice. In addition to monitoring performance in general, PIs are essential for managing the performance of staff over time, and more specifically the gap between expected performance and actual performance measured. Individual clinics should determine which indicators are key to the success in their organisation based on their patient population, protocols, and procedures, and as such, which are their KPIs. LIMITATIONS REASONS FOR CAUTION: The consensus values are based on data found in the literature and suggestions of experts. When calculated and compared to the competence/benchmark limits, prudent interpretation is necessary taking into account the specific clinical practice of each individual centre. WIDER IMPLICATIONS OF THE FINDINGS: The defined PIs complement the earlier defined indicators for the ART laboratory. Together, both sets of indicators aim to enhance the overall quality of the ART practice and are an essential part of the total quality management. PIs are important for education and can be applied during clinical subspecialty. STUDY FUNDING/COMPETING INTERESTS: This paper was developed and funded by ESHRE, covering expenses associated with meetings, literature searches, and dissemination. The writing group members did not receive payment.Dr G.G. reports personal fees from Merck, MSD, Ferring, Theramex, Finox, Gedeon-Richter, Abbott, Biosilu, ReprodWissen, Obseva, PregLem, and Guerbet, outside the submitted work. Dr A.D. reports personal fees from Cook, outside the submitted work; Dr S.A. reports starting a new employment in May 2020 at Vitrolife. Previously, she has been part of the Nordic Embryology Academic Team, with meetings were sponsored by Gedeon Richter. The other authors have no conflicts of interest to declare. DISCLAIMER: This document represents the views of ESHRE, which are the result of consensus between the relevant ESHRE stakeholders and where relevant based on the scientific evidence available at the time of preparation.The recommendations should be used for informational and educational purposes. They should not be interpreted as setting a standard of care, or be deemed inclusive of all proper methods of care nor exclusive of other methods of care reasonably directed to obtaining the same results. They do not replace the need for application of clinical judgment to each individual presentation, nor variations based on locality and facility type.Furthermore, ESHREs recommendations do not constitute or imply the endorsement, recommendation, or favouring of any of the included technologies by ESHRE.
Keywords: IVF/ICSI; ART; ovarian stimulation; consensus; data collection; key performance indicators; quality management; performance